Genetic Polymorphism of Calpastatin (CAST) Gene in Pasundan Cattle - Slamet Diah Volkandari; Aina Nadila; Nani Radiastuti; Endang Tri Margawati (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
The aim of this study was to determine genetic diversity of Calpastatin gene (CAST) in Pasundan cattle. Forty-four fresh blood samples were collected from UPTD BPPT Beef Cattle Ciamis West Java. Genomic DNA samples were extracted using High Salt method. A 523 bp fragment of Calpastatin gene was successfully amplified using PCR method. Genotyping of CAST gene was conducted by PCR-RFLP method using RsaI restriction enzyme (GT^AC). Genotypes and alleles were analyzed using software Cervus 3.0.7. Parameters were observed i.e genotypes and alleles frequencies, heterozygosity observed (Ho) and expected (He), Hardy Weinberg Equilibrium (HWE), and Polymorphic Information Content (PIC). Result showed that three variant genotypes of GG, GC and CC were found and two variant alleles of G and C. Allele G was found higher (0.77) than allele C (0.23). Population of Pasundan cattle was found polymorphism and in the Hardy Weinberg Equilibrium. Polymorphic Information Content (PIC) value showed in a moderate (0.290) condition. Values of Heterozygosity observed and expected were 0.409 and 0.355 respectively. This research concludes that there is polymorphism of CAST gene in Pasundan cattle population and has genetic diversity. This result could be used as early genetic information in exploration of Pasundan cattle.